Match running performance on three different competitive standards in Norwegian soccer - Sæterbakken, A.; Haug, V.; Fransson, D.; Grendstad, H. N.; Stokvold Gundersen, H.; Fusche Moe, V.; Ylvisaker, E.; Shaw, M.; Riiser, A.; Andersen, V. (Sports Medicine International Open, 2019)
The aim of the study was to compare running performance of three competitive standards and to examine the effects of being promoted to a higher league in Norwegian football. One club's first and second team were included. The first team consisted of professional soccer players playing at Level 2 (2015 season) and Level 1 (2016 season). The second team consisted of amateurs playing at Level 4. A fully automatic tracking system was used to examine running performance, divided into different running-speed categories and playing position. Forty-one matches were included containing 278 observations. Level 1 performed 61 and 51% sprinting compared to Level 2 and Level 4 but similar high-speed running. Similar high-speed running distances were observed only for the different playing positions at Level 1 compared to Level 2 and 4. The sprinting distance was greater for the central defender and attacker, and the number of accelerations was greater for central midfielders and wide midfielders` playing at Level 1 compared to lower competitive standards. In conclusion, better competitive standards resulted in greater high-intensity actions than lower leagues in Norwegian soccer. Furthermore, only central defenders and attackers increased their high-intensity locomotions when the team was promoted.